A competitive dynamics perspective on the diversification of third-party logistics providers' service portfolios. (February 2021) - Barker, Jordan M.; Gibson, Andrew R.; Hofer, Adriana R.; Hofer, Christian; Moussaoui, Issam; Scott, Marc A.
Highlights: Rivalry among 3PLs is a driver of 3PL service diversification. Peers' service additions lead focal 3PL to subsequently add new services. Peers' service additions that mimic focal 3PL offering trigger greater responses. Similarity of focal 3PL and peers' service offerings moderates these effects. Abstract: The diversification of service portfolios is one of the key strategies employed by third-party logistics providers (3PLs) to remain competitive. Moving from traditional transportation and warehousing services, many 3PLs now offer a one-stop shopping experience to shippers by combining these services with customized offerings such as inventory management, integrated supply chain management, and consulting. Academic literature has identified key drivers of this phenomenon, such as the need to meet shippers' increasing expectations, a 3PL's strategic orientation, or to capitalize on existing resources and capabilities. Yet, work focused on the theoretical and empirical analysis of competitive drivers of 3PL diversification is scant. Grounded in competitive dynamics theory and the theory of strategic groups, we investigate the effects of the addition of new services by peer 3PLs on a focal 3PL's diversification of service offerings. In particular, we hypothesize—and find based on the analysis of a large archival panel dataset—that a focal 3PL is more likely to expand its service portfolio when its peers introduce services that put them in direct competition with the focal 3PL. The same behavior is observed, though to a lesser extent and with longer time lags, when peers introduce services that the focal 3PL did not previously offer. The results also indicate that when there is greater similarity between the service portfolios of a focal firm and its peers, these relationships will be stronger. Collectively, these findings contribute to the logistics outsourcing and diversification literatures and offer refinements to competitive dynamics theory. Our work also offers managerial insights relevant to 3PL decision makers as they design their service portfolios.